SOSIALISASI KESEHATAN TERNAK DI DESA KONDOANO KECAMATAN MOWILA KABUPATEN KONAWE SELATAN - Bain, Ali; Sani, La Ode Arsad; Zulkarnain, Deki; Kurniawan, Widhi; Has, Hamdan; Abadi, Musram; Munadi, La Ode Muh (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The Community Service Activity of Halu Oleo University Thematic KKN lecturers in 2024 aims to provide information to livestock farmers in Kondoano Village, Mowila District, South Konawe Regency, regarding livestock health and disease control. The activity lasted for one month, from July to August 2024, and included socialization of livestock health which was carried out in two stages: preparation and implementation. The results of the activity showed high enthusiasm from the participants, with farmers actively participating in the question and answer session about livestock health and potential diseases. This socialization provided new knowledge to farmers regarding livestock health and how to handle it, which contributed to reducing livestock disease and mortality. Livestock health is an important factor in the development of livestock businesses, and by ensuring livestock health, farmers can operate without obstacles.